Distribution of phytoplankton in Kuantan port during northeast monsoon season - Hamzah, Amir Safwan; Mohammad Noor, Normawaty; Adam, Aimimuliani; Ahmad, Zuhairi (2018)
Harmful algal bloom (HAB) is a proliferation of phytoplankton that can produce biotoxins and cause harm to human health, as well as the environment and the organisms associated with it. The first case of HAB in Kuantan Port was recorded on November 2013, followed by another outbreak on August 2014. This study aims to investigate the phytoplankton distribution and dispersal in Kuantan Port during the Northeast monsoon season in order to identify how far the HAB can spread in case such an event would ever occur again. Phytoplankton samples were taken at Kuantan Port from three levels of depth (surface, middle, and bottom) from every hour during a period of 24 hours. Samples were preserved in Lugol’s iodine. Physico-chemical properties such as temperature, salinity, pH, dissolved oxygen (DO), total dissolved solid (TDS), turbidity, total suspended solid (TSS), and nutrients (phosphorus, nitrate, nitrite, ammonia) were also taken during each sampling. Phytoplankton samples were counted and identified up to genus level. Simulation of phytoplankton dispersal in Kuantan Port was conducted using the program MIKE 21. Thirty-eight taxa of phytoplankton were identified. Phytoplankton concentration ranged from 124 cells/L to 775 cells/L. TSS value ranged from 0.0345 g to 0.0110 g. Phosphorus concentration ranged from 0.075 mg/L PO4 to 3.82 mg/L PO4. Nitrate concentration ranged from 1.05 mg/L NO3 -N to 2.45 mg/L NO3 -N. Nitrite concentration ranged from 0.0040 mg/L NO2 -N to 0.0095 mg/L NO2 -N. Ammonia concentration ranged from 0.045 mg/L NH3 -N to 0.140 mg/L NH3 -N. Analysis of Variance shows that there are significant differences across sampling time for each nutrient. This study recorded the presence of several HAB species such as Dinophysis sp, Noctilluca sp, and Prorocentrum sp. The presence of these species further indicates that several safety measures need to be considered to safeguard public health, particularly in Pahang coastal waters.